MANAGEMENT OF THE PEDAGOGICAL TEAM IN GENERAL SECONDARY SCHOOLS - AS A SOCIO-PEDAGOGICAL CONDITION - Muzaffar Ummatovich Kurbanov (Galaxy International Interdisciplinary Research Journal, 2023)
The article generalises theoretical and practical research and offers a new solution to the problem of management of pedagogical team in schools, which is revealed in creating pedagogical conditions for the development of the pedagogical team. Today, democratization of education is one of the main principles of its development, which ensures the expansion of the rights and obligations of the teacher and the student, and the implementation of the principles of cooperation between the leader, the teacher and the student. Both democratization and humanization recognize that all people are different, and true equality consists of the right and opportunity for everyone to develop and realize their full potential in life.